Application of Organizational Culture in the Police Unit of Pamong Praja (Satpol – PP) district of Pohuwato - Rusni Djafar; Umar Sune (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2023)
The results of the research conducted by the researchers through the dissemination of the list of interviews of seven organizational cultural indicators described through the statement of the informant on the research site, namely in the environment of officers of the Police Unit of Pamong Praja district of Pohuwato, can be explained as follows. In response to the innovations and courage in taking risks, the leadership of joint officials in the environment has had the ability to innovate in the framework of the implementation of tasks in the Police Unit Office Pamong Praja Pohuwato district, for example in terms of the arrangement of the PSK-PSKs in a certain cafe-cafe that has been considered to have innovated against the handling of this problem where they were initially affected by the raids collected in the Satpol PP Office to be given to the builder as well as guidance by the head of the Office in particular by the fields in relation to the problem then returned to its place of origin, but a few months later they re-acted in the café-café so that there was no effect they were conducting on the case.